Information dissemination workshops and dialogues with SMEs and finance institutions in Zambia - Mudege, Netsayi N. (Accelerating Impacts of CGIAR Climate Research for Africa, 2021)
This report collates the results of the discussions generated during the information dissemination meeting. All SMEs that participated in the information session are interested in applying for the innovation grant and contributing to AICCRA's objectives. However, extra effort should be made to ensure that gender is integrated into the applications and partnerships formed to apply for the grant. The report also clearly outlines and discusses the climate-related challenges faced in the different regions and how to address these. For example, the Northern and Luapula provinces face increased rainfall, longer rain seasons, lower temperatures and strong winds, affecting agriculture and aquaculture in various ways. The Southern province is plagued by drought and dry spells. Different climate change mitigation approaches and climate-smart information are needed to address the challenges plaguing the different regions. The need for appropriate finance mechanisms for climate adaptation can hardly be overemphasized. The regional focus of some CSA bundles needs to be expanded. For example, although CSA bundle 1 focuses on Lusaka, Eastern and Central, SMEs in the Northern and Luapula provinces also mentioned the need for pumps to cater to different water problems such as flooding and lack of consistent distribution and availability of water throughout the year. The project could also promote citizen science to ensure that SMEs and farmers collect relevant climate data and upload it into a database where it can be interpreted to generate appropriate CSI messages to SMEs and smallholder farmers.